STRATEGI PENGUATAN PENDEKATAN HUMANISTIK SEBAGAI UPAYA MEMBANGUN KARAKTER YANG INKLUSIF DI PERGURUAN TINGGI - Muliastrini, Ni Ketut Erna (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
The challenges of higher education today in Indonesia are not only related to the classic problems that include equality and fulfillment of access, infrastructure and financing of education, but also to the quality of graduates who must have qualified intellectuals in their fields as well as high morality. Seeing these conditions, the availability of human resources with character and a humanistic campus climate are very important needs. This is certainly done to prepare for global challenges and national competitiveness. Universities must be able to prepare a generation that has good abilities and character. Thus, the humanistic approach is expected to be one of the implemented solutions in lectures by prioritizing the humanistic approach. In practice, of course, it requires integrated planning. The implementation of strengthening the humanistic approach along with continuous follow-up must also be prepared as optimally as possible in order to create an inclusive character in Higher Education. With the right strategy, universities can create graduates who are not only intellectually intelligent but also have an inclusive, tolerant, and empathetic character, who are ready to contribute to a diverse society. Keywords: inclusive character, humanistic approach, universities.